Straßenbenutzungsgebühren aus Sicht europäischer Städte. Bedürfnisse, Anforderungen und Probleme bei der Einführung. - Schade, Jens; Obst, Denise (Deutscher Verkehrs-Verl., 2009)
Straßenbenutzungsgebühren stellen den Versuch einer Internalisierungsstrategie dar, über flexible, variable und verhaltensnahe Systeme eine Anlastung der tatsächlich anfallenden Kosten der Autonutzung zu erreichen. Dies würde zum einen die Möglichkeit eröffnen, das Nachfragewachstum des motorisierten Individualverkehrs zu reduzieren, zum anderen wäre über eine Differenzierung der Preise in gewissem Ausmaß eine räumliche und zeitliche Lenkung der v. a. in städtischen Ballungsräumen problematischen Pkw-Nachfrage zu erreichen (Travel Demand Management). Darüber hinaus ermöglichen sie über die Generierung von Einnahmen die Finanzierung angebotsorientierter Alternativen zum Pkw, die aufgrund der angespannten Situation der öffentlichen Haushalte sonst nur schwer realisierbar sind.

An analysis of users' needs has established the demands, requirements and problems of European cities and regions concerning the introduction of municipal road user charges. This survey - carried out as part of the EU Project "CURACAO" - highlights the guarantee for transport systems' efficiency, improvements to environmental conditions and the quality of life in cities as the principal goals of the charging system. With regard to the use of the forthcoming revenue, the majority response has been that it should be allocated primarily to public transport. Most of the cities questioned about the adoption of the charging system, have stipulated that they prefer known solutions of a technical nature in preference to non-technical ones such as written authorizations in the form of "vignettes". Most cities are in the early stages of implementing a charging system, and relevant plans for its adoption are under way. Only two cities have adopted a "Road Pricing System" so far. Among the main reasons given for the reluctance to adopt such a system is the lack in its acceptance by the public and the authorities as well as the enormous expenditure associated with planning and managing such a project. In order to assist cities with the process of introduction, the CURACAO Project can offer relevant information and reports about road user charges and their introduction. The parties questioned have shown interest in the project, the focus being on information related to its acceptance, commercial impact and benefits, as well as political ambitions.
Road user charges and the views of European cities.
Keywords: Verkehr; Individualverkehr; Autoverkehr; Stadtverkehr; Verdichtungsraum; Innenstadt; Großstadt; Verkehrsnachfrage; Straßenverkehr; Befragung; Gebühr; Preispolitik; Straßenbenutzungsgebühr; Maut; Road Pricing; Akzeptanz; Preisgestaltung